Banco de germoplasma preliminar de plantas útiles de tipo herbáceo silvestre in situ, en el área de la maná - Narváez Solano, José Luis (2010)
The location and identification of herbaceous plants wild for the investigation of the potential for uses and the subsequent design and layout for a bank germplasm was conducted at the systems level agroforestry in the parishes of Guasaganda, Pucayacu and Carmen, that structure the rural area of the canton Maná (Province of Cotopaxi) with an altitude between 240 to 686. We used a preferential rate sampling, for which is implemented a total of six transects of vegetation 10 x 100 m (1,000 m 2 each), so that demarcated a total of two transects in each of the areas selected surrounding parishes. A total of 56 species with some use known, at a total of 48 genera and 27 families ; A phytosociological level, species with higher values of importance were Impatiens balsamina (Family Balsaminaceae), Eryngium foetidum (Apiaceae Family) and Sida acuta (Malvaceae family). To make the design of in situ gene bank was used the following methodology: actual use species in relation to biological forms Raunkaier. The area looked gene bank use 3, 267.00 m2.